2013
DOI: 10.1371/journal.pone.0067175
|View full text |Cite
|
Sign up to set email alerts
|

The Continuum of Maternal Sepsis Severity: Incidence and Risk Factors in a Population-Based Cohort Study

Abstract: ObjectiveTo investigate the incidence and risk factors associated with uncomplicated maternal sepsis and progression to severe sepsis in a large population-based birth cohort.MethodsThis retrospective cohort study used linked hospital discharge and vital statistics records data for 1,622,474 live births in California during 2005–2007. Demographic and clinical factors were adjusted using multivariable logistic regression with robust standard errors.Results1598 mothers developed sepsis; incidence of all sepsis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
139
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 183 publications
(157 citation statements)
references
References 34 publications
14
139
2
2
Order By: Relevance
“…The association between sepsis and parity, which was not explained by age, ethnicity, employment status, smoking or BMI in our study, appears to be inconsistent in the literature, with studies finding increased risk for multiparous9 or nulliparous women 6, 10. This may be due to differences in the study populations, methods or adjustment for confounding.…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…The association between sepsis and parity, which was not explained by age, ethnicity, employment status, smoking or BMI in our study, appears to be inconsistent in the literature, with studies finding increased risk for multiparous9 or nulliparous women 6, 10. This may be due to differences in the study populations, methods or adjustment for confounding.…”
Section: Discussioncontrasting
confidence: 87%
“…These include studies of sepsis in obstetric populations,6, 9, 10, 11, 30 and other morbidities in obstetric populations 12, 13, 14, 27, 31, 32. Interestingly, all those studies found an effect of at least one socio‐demographic factor, most commonly age, body mass index (BMI) or ethnicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,[99][100][101] Sepsis is estimated to cause 9.7% of maternal deaths in Africa, 11.6% in Asia and 7.7% in Latin America and the Caribbean combined. 102 In 2006-8, the UK maternal mortality rate from genital tract sepsis was 1.13/100,000 maternities, a rate not seen since the early 1970s, 100,103 and in 2009-12, one-quarter of all maternal deaths were due to infectious causes.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work has suggested an approximate doubling of the incidence of maternal sepsis in the USA since 2003. 99 Key information gaps in the understanding of this pressing problem are the number of women affected, causative organisms, sources of infection and risk factors for severe sepsis and poor outcomes such as septic shock. Sepsis progresses along a spectrum of severity, so clarity about these factors has urgent implications for clinical management and infection control strategies to avoid preventable maternal deaths.…”
Section: Introductionmentioning
confidence: 99%